2021
DOI: 10.3748/wjg.v27.i17.1920
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence applications in inflammatory bowel disease: Emerging technologies and future directions

Abstract: Inflammatory bowel disease (IBD) is a complex and multifaceted disorder of the gastrointestinal tract that is increasing in incidence worldwide and associated with significant morbidity. The rapid accumulation of large datasets from electronic health records, high-definition multi-omics (including genomics, proteomics, transcriptomics, and metagenomics), and imaging modalities (endoscopy and endomicroscopy) have provided powerful tools to unravel novel mechanistic insights and help address unmet clinical needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 92 publications
1
49
0
Order By: Relevance
“…A broad spectrum of applications of AI in inflammatory bowel disease was also reviewed by Gubatan et al [ 21 ] as we demonstrated in Figure 7 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A broad spectrum of applications of AI in inflammatory bowel disease was also reviewed by Gubatan et al [ 21 ] as we demonstrated in Figure 7 .…”
Section: Discussionmentioning
confidence: 66%
“… Location of artificial intelligence (AI) in the medical management of inflammatory bowel disease as proposed by Gubatan et al [ 21 ]. IBD, inflammatory bowel disease.…”
Section: Figurementioning
confidence: 99%
“…43 In recent years, there has been an increasing emphasis on identifying clinical and biological markers that accurately predict patient response to certain IBD treatments. 44 This is particularly important for tailoring the treatment regimen to each patient. Several studies have evaluated utility of prediction models for response to vedolizumab therapy.…”
Section: Anti-integrin Therapy: Vedolizumab (Anti-α4β7)mentioning
confidence: 99%
“…The integration of data from individual IBD-relevant ‘omes’ is currently considered as the approach that would significantly improve the understanding of IBD pathogenesis and management [ 1 , 13 , 21 ]. One of the key challenges in this process is to effectively utilize information obtained in omics studies with patients’ data stored in electronic medical records (biochemistry tests, various imaging data, symptoms at diagnosis and lifestyle specifics) [ 38 , 91 ]. Machine learning approaches offer the ability to effectively deal with the high dimensionality of these data with the final aim to translate discoveries into clinical practice.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The underlying genetic predisposition to IBD has not been completely revealed employing only the candidate gene approach or genome wide association studies (GWAS). For that reason, there is great interest in the application of AI in IBD research with the goal to improve: patient identification, differential diagnosis, disease risk prediction and clinical outcomes and classification of disease subtypes, as well as identification of disease biomarkers that could be targeted for advancing therapeutic management ( Figure 1 ) [ 1 , 28 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%